Cardiovascular responses to injections of angiotensin II or carbachol into the rostral ventrolateral medulla in rats with AV3V lesions - Vieira, Alexandre Antonio [UNESP]; Colombari, Eduardo [UNESP]; De Luca, Laurival A. [UNESP]; Colombari, Debora S. A. [UNESP]; De Paula, Patricia M. [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2013)
Injection of L-glutamate (GLU) into the rostral ventrolateral medulla (RVLM) produces sympathetically-mediated pressor responses that depend on the integrity of the tissue surrounding the anteroventral third ventricle (AV3V region). The injection of angiotensin II (ANG II) or the cholinergic agonist carbachol into the RVLM also produces pressor responses. In the present study, we investigated if the lesion of the AV3V region affects the pressor responses to ANG II or carbachol injected into the RVLM in unanesthetized rats. Male Holtzman rats with sham or electrolytic AV3V lesions and a stainless steel cannula implanted into the RVLM were used. The pressor responses to ANG II (200 ng/100 nl) injected into the RVLM were reduced by acute (1 day) (12 +/- 3 vs. sham lesions: 26 +/- 4 mmHg) or chronic (15 days) AV3V lesions (12 +/- 5 vs. sham lesions: 27 +/- 4 mmHg), whereas acute or chronic AV3V lesions did not affect the pressor responses to carbachol (1 nmol/100 nl) injected into the RVLM. The present results suggest that the AV3V region modulates the excitability of the RVLM neurons involved with the pressor response produced by the activation of angiotensinergic mechanisms in this area. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Sympathetic; RVLM; Angiotensinergic; Pressor response; Hypertension